Debunking the assumption “if the patient survives the ICU everything will be fine” (Paliativní medicína, 2023)
Critical illness is a traumatic moment in a patient’s life – often experienced as a life-threatening event. The initial decision to offer ICU admission and associated conversations with families are often focused on the probability of the patient surviving the ICU stay. However, ICU survivors face a higher risk of mortality even after discharge from the ICU and are often confronted with persistent physiologic, functional and neuropsychological sequelae.